Phet Learning Media on Science Learning Outcomes Material Electrical Circuits in Madrasah Ibtidaiyah - Wakhidah, Nur; Adawiyah, Rubbiatul; Rohmania, Umiatur; Rahma, Talita Dwi; Rahayuningsih, Vina; Lathifah, Lathifah; Safitri, Ani; Chotimah, Khusnul (Indonesian Journal of Science Learning (IJSL), 2024)
The results of interviews with teachers of class VIA stated that students of class VIA found it challenging to learn simple electrical circuit material because the media used in the science learning process only used mind-media mapping. The purpose of this study was to determine the effect of PhET ( Physics Education Technology) learning media on science learning outcomes for students in class VI- A of simple electrical circuits at MINU Waru I. This study used quantitative research. The method used is the Pre-Experimental Design experimental method in the form of One Group Pretest - Posttest. Data collection techniques used in this study were through observation, interviews, and tests. Meanwhile, the data analysis techniques used were a normality test, homogeneity test, and non-parametric Wilcoxon signed rank test statistical test. Teach science simple electrical circuits material